Factor-Independent Assembly of Elongation-Competent Ribosomes by an Internal Ribosome Entry Site Located in an RNA Virus That Infects Penaeid Shrimp - Cevallos, Randal C. (American Society for Microbiology, 2005)
The Taura syndrome virus (TSV), a member of the Dicistroviridae family of viruses, is a single-stranded positive-sense RNA virus which contains two nonoverlapping reading frames separated by a 230-nucleotide intergenic region. This intergenic region contains an internal ribosome entry site (IRES) which directs the synthesis of the TSV capsid proteins. Unlike other dicistroviruses, the TSV IRES contains an AUG codon that is in frame with the capsid region, suggesting that the IRES initiates translation at this AUG codon by using initiator tRNA(met). We show here that the TSV IRES does not use this or any other AUG codon to initiate translation. Like the IRES in cricket paralysis virus (CrPV), the TSV IRES can assemble 80S ribosomes in the absence of initiation factors and can direct protein synthesis in a reconstituted system that contains only purified ribosomal subunits, eukaryotic elongation factors 1A and 2, and aminoacylated tRNAs. The functional conservation of the CrPV-like IRES elements in viruses that can infect different invertebrate hosts suggests that initiation at non-AUG codons by an initiation factor-independent mechanism may be more prevalent.